THE CHALLENGES AND STRATEGIES OF THE STUDENTS IN THE TRANSLATION PROJECT - Sinta Ria; Yelia; Rosinta Norawati (Program Studi Pendidikan Bahasa Inggris, 2025)
Translation projects are essential in preparing students for real-world language services, especially within project-based learning contexts. However, a gap still exists between theoretical instruction and the practical challenges students face during such projects. This study explores the challenges encountered by English Education students at Universitas Jambi and the strategies they used to overcome them. Employing a qualitative case study design, the research involved students enrolled in the Project in Language Services course during the even semester of the 2023/2024 academic year. Data were gathered through semi-structured interviews with three student groups. The analysis identified four main categories of challenges: linguistic (e.g., technical terms and sentence structure), cultural (e.g., cultural expressions), technological (e.g., tone inaccuracies in machine translation), and managerial (e.g., time constraints and client communication). To address these, students used strategies such as consulting academic references, applying semantic techniques, collaborating with peers and lecturers, and using digital tools. The findings conclude that while translation projects expose students to real-world challenges, the integration of adaptive strategies enhances their problem-solving skills, autonomy, and preparedness for professional translation work.